If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 10 = 15y Reorder the terms: 10 + 5x = 15y Solving 10 + 5x = 15y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5x = -10 + 15y Combine like terms: 10 + -10 = 0 0 + 5x = -10 + 15y 5x = -10 + 15y Divide each side by '5'. x = -2 + 3y Simplifying x = -2 + 3y
| 169=144+x^2 | | -7(7x-10)=609 | | 45/48.15=x/100 | | 1/3y=6-3x | | .4/.04 | | 400=m+310 | | 6(-3+x)=48 | | 4-5w=-6 | | a+-7+2a+-7+17+a+17=360 | | 221=m+76 | | -3(3x-1)=-7x-5 | | 15pt=c | | y=6x^2-4x-1 | | r/-164=50 | | 4m-3m+2m-m+3=2m+7-6+2 | | a-7+2a-7+17+a+17=360 | | -240=-6(4k+8) | | P=m-2p/2 | | x=1%(32.79) | | 48.15-45= | | 3G=18.3 | | 4d^2+8d-2cd=0 | | 33.77=y%(32.79) | | .03xx/10=1/2x-0.4 | | -10=-6+4u | | ln(x)+ln(x+6)=ln(5x+12) | | 4g+g-3G-g=16 | | -7(7+4x)=-273 | | 3t+6t-8t-1=13 | | 15q-3q-19q-2q+q-1=2 | | -4(-5-6x)=236 | | 4x+22=7x-50 |